Analisis Kelayakan Usaha Pembenihan Ikan Patin Di Kelurahan Margorejo Kecamatan Metro Selatan - Indra Tri Pangestu; Zulkarnain Zulkarnain; Ainul Mardliyah (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2022)
The purpose of this study was to analyze the feasibility of catfish hatchery business in in Margorejo South Metro District. The research was conducted in Margorejo South Metro District with a total sample of 30 people. The sampling method is saturated sampling (census) and the analysis used is financial feasibility analysis. The results of the analysis of the catfish hatchery business are profitable and feasible to continue financially (NVP, IRR, Net B/C, Gross B/C and PP). Catfish hatchery business from the aspect of market and marketing has promising potential